SIFAT FISIKO-KIMIA MINYAK KERUING YANG DIHASILKAN DARI METODE PENYULINGAN UAP (The physico-chemical properties of Keruing oils obtained by steam distillation technique) - Bambang Wiyono (Jurnal Penelitian Hasil Hutan, 1996)
Keruing  oils can be obtained  through separating  the oil from keruing gum  by distillation technique,   or distilling  keruing  wood.  In accordance with the lattest method,   the objective of this research  is to study the  physico-chemical  properties  of keruing oils which were obtained by steam distillation  of   a mixture of several keruing wood species.  This wood was randomly taken three  times from  the wastes of wood processing  industry in East Kalimantan.   Each wood wastes taken was steam distilled  and  the yielded  oils were   analysed  their physico-chemical properties.   The difference between means value  of the properties of the oils  was tested by using LSD according td SAS  procedure.Results   revealed that  wood wastes gave  a highly  significant  effect on refractive  index, optical  rotation,  acid and  ester number  of keruing  oils.  It also gave  a significant  effect  on saponification   number.   Further  analysis   showed  that  the  keruing  oil  with  clear  colour compared  to  both  keruing  oil  with  clear yellow and pale  yellow  colour  was  a  significant difference in acid   and ester number.  Moreover,  the keruing oil with pale yellow  colour had ll significant  difference  in saponification   number  compared  the others.  Among  these  oils,  the refractive index and optical rotation properties  were a significant  difference one to the others. Based these results,  if  the keruing wood wastes will be used as raw materials for  keruing oil production,  it is better that the keruing wood containing much oil or gum should  be separated from the others before further processing.Keywords:  Keruing  oil, Dipterocarpus  spp, Steam distillation, oil properties